Sanksi Pidana Perzinahan Akibat Adanya Delik Aduan dari Pihak yang Dirugikan Menurut Pasal 284 Kuhp - Muhammad Ridho Muttaqien; Anyelir Puspa Kemala (Syntax Literate, 2023)
This study aims to obtain information and analyze the law regarding the criminal sanctions for adultery due to complaints from the injured party according to Article 284 paragraph (1) of the Criminal Code. One of the regulated behaviors related to adultery in marriage is adultery in the context of Islamic law and overspel in criminal law literature. The rampant adultery in public life has tarnished the existence of a sacred bond in marriage. "With the existence of a marriage, it is hoped that it can create a tera family, therefore a law on marriage was formed. A husband and wife who are convicted of adultery, one of the aggrieved can report the spouse through the police. Regarding the sanctions that can be received by adulterers, referring to the provisions of Article 284 of the Criminal Code, the perpetrators are threatened with imprisonment for a maximum of nine months. This applies to both husband and wife who are having an affair. If adultery has led to adultery, then the spouse of the spouse who committed adultery can report his wife/husband and infidelity to the police on the basis of adultery as stipulated in Article 284 of the Criminal Code (KUHP). Article 284 of the Criminal Code is an absolute complaint offense, meaning that it cannot be prosecuted if there is no complaint from the aggrieved and/or humiliated husband or wife. In addition, overspel criminal reports cannot be processed further by the Police if the reporting person is not the official spouse of the injured party.